Comparing acceptance of smoking cessation and smoke-free home intervention offers and associated factors among people with low income in the USA: baseline results of a randomised controlled trial - Matthew W Kreuter; Michelle C Kegler; Jennifer Wolff; Amy McQueen; Lauren Grimes; Enguday Teshome; Rachel Garg; Tess Thompson; Kelly Carpenter (BMJ Public Health)
Introduction State tobacco quitlines are the most commonly available smoking cessation programmes; however, they have low reach and typically only enrol people who are ready to quit in the next 30 days. Expanding quitline services may increase the total number of people engaged in tobacco control efforts and the number who eventually quit. In this randomised controlled trial, we offered both arms a tobacco quitline intervention. In arm 2, if they declined the quitline, we then offered a smoke-free home (SFH) intervention. We examined the number of participants who accepted each intervention offer at baseline and whether acceptance varied by participant characteristics.Methods We recruited 1982 people who called 211, a social services helpline for social needs; mean age=50, 68% female; 45% white, 41% black and 14% other race/ethnicity; 68% reported an annual household income <US$20 000.Results In each arm, 59.7% of participants accepted the quitline offer. In arm 2, among those who declined the quitline offer, 53.1% accepted the SFH intervention offer. Thus, an additional 212 (21.4% of all arm 2 participants) people who smoke engaged in tobacco control programmes than would have with standard practice alone (quitline only). Acceptance differed by participant characteristics: males were less likely than females to accept either offer. Whites were less likely, and older adults and those with greater nicotine dependence were more likely, to accept the quitline offer.Conclusions Proactive approaches identified many low-income people who smoke and offering an SFH intervention retained many more of them in tobacco control efforts. Future trial results will assess intervention engagement and effects on cessation.Trial registration number ClinicalTrials.gov identifier NCT04311983.